2014
DOI: 10.1007/s10584-014-1253-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the shadow of experience of extreme weather events

Abstract: Climate change will increase the frequency and/or intensity of certain extreme weather events, and perceived experience with extreme weather may influence climate change beliefs, attitudes, and behaviors. However, the aspects of extreme events that influence whether or not people perceive that they have personally experienced them remain unclear. We investigate (1) the correspondence of reported experience of extreme weather events with documented events, and (2) how characteristics of different extreme events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 30 publications
(30 reference statements)
1
52
0
Order By: Relevance
“…Similarly, whilst there is not an extensive assessment of the spatial attributes of risk perception within the wider naturalhazard literature, consideration has been given to proximity or real distance from the source of the hazard, including volcanoes, (57)(58)(59) air quality, (60)(61)(62) earthquakes, (63)(64)(65) debris flows, (66) hurricanes, (39,67) groundwater pollution, (68,69) and hurricane, tornado, and drought. (70) More specifically, in the context of a potential volcanic hazard, Perry et al (59) do not find any significant relationship between real distance and perception, although Peacock et al, (39) in relation to hurricane-risk perception, find proximity to wind hazard zone to be a significant determinant. Interestingly, a study by Trumbo et al (71) exploring the effect of proximity on hurricane outlook and optimistic bias (i.e., affective components of risk perception) found distance to have only a small influence and similarly Suls et al (72) found participants living closer to a tornado reported more vulnerability in a study about optimism following tornado disasters.…”
Section: Risk Perception and Proximitymentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, whilst there is not an extensive assessment of the spatial attributes of risk perception within the wider naturalhazard literature, consideration has been given to proximity or real distance from the source of the hazard, including volcanoes, (57)(58)(59) air quality, (60)(61)(62) earthquakes, (63)(64)(65) debris flows, (66) hurricanes, (39,67) groundwater pollution, (68,69) and hurricane, tornado, and drought. (70) More specifically, in the context of a potential volcanic hazard, Perry et al (59) do not find any significant relationship between real distance and perception, although Peacock et al, (39) in relation to hurricane-risk perception, find proximity to wind hazard zone to be a significant determinant. Interestingly, a study by Trumbo et al (71) exploring the effect of proximity on hurricane outlook and optimistic bias (i.e., affective components of risk perception) found distance to have only a small influence and similarly Suls et al (72) found participants living closer to a tornado reported more vulnerability in a study about optimism following tornado disasters.…”
Section: Risk Perception and Proximitymentioning
confidence: 98%
“…In relation to the second approach to the analysis of the spatial components of risk, creating maps of data from survey questionnaires (70) facilitates the aggregation of multiple individual respondents' risk perception (of natural or technological hazard sources) in order to discover whether the data's graphic visualization and analysis demonstrate any discernible spatial patterns. It can also assist with analysis of whether the aggregate representation of community perception of a hazard risk can usefully inform future hazard-risk management.…”
Section: Spatial Representation Of Survey Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It seems unlikely that climate models will be able to provide the local-scale, specific, reliable, and trusted information required for most private adaptation decisions. Instead, direct experience of weather events is likely to be an important information source, with several studies suggesting a link between experience of weather anomalies and stated belief in climate change (Howe et al, 2014;McCright et al, 2014;Kaufmann et al, 2017). Therefore, how well people learn from experience in nonstationary, stochastic environments has important implications for the rate of adaptation and the economic costs associated with climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Although not reviewed here, it should be noted that there is complementary research on how people's experiences, including with extreme weather, influence their climate change risk perceptions and behaviors (84)(85)(86). …”
mentioning
confidence: 99%